Artists for Artists: Fifty Years of the Foundation for Contemporary Artists - Banks, Eric (New York Foundation for Contemporary Arts, 2013)
Published in 2013 on the occasion of the Foundation's 50th Anniversary, Artists for Artists: Fifty Years of the Foundation for Contemporary Arts is a 208-page scholarly book that chronicles FCA's impact on generations of performing artists, made possible by generations of visual artists.It includes an oral history compiled from interviews with original Board members, commissioned essays, ephemera from FCA's early public performances, and over 200 photographs of performances and other work supported by the Foundation, many of which are previously unpublished. During the research for the book, original recordings were discovered from the "Six Lectures" series which the Foundation sponsored and organized at the 92nd Street Y in 1966. These talks, by Buckminster Fuller, Marshall McLuhan, N.O. Brown, and others, have been transcribed for the first time and form the middle section of the book, accompanied by never-seen photo documentation of each evening. Artists for Artists also features two dozen profiles of Grants to Artists recipients from the last twenty years, a chronology, a history of grants made, and an index of the 900+ artists who contributed work to benefit exhibitions to support these grants, and a checklist from the historic first benefit exhibition at the Allan Stone Gallery in February 1963, which was perhaps the first benefit exhibition ever.